Pelatihan Pemanfaatan Mesin Pencacah Pakan Ternak (Choper) untuk Meningkatkan Efektifitas Pakan Sapi bagi Kelompok Tani “Loh-Jinawi’ di Desa Sambigede Kecamatan Sumberpucung Kabupaten Malang - Yoto Yoto; Marsono Marsono; Agus Suyetno; Putri Ardista Nursisda Mawangi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Enumeration of feed in large quantities requires a relatively long enumeration time so that the fulfillment of feed requirements for livestock in large quantities is not optimal. In addition to the enumeration process, problems that often arise are the result of less refined feed enumeration because large quantities of feed enumeration still use manual methods or human power. Assistance and training Training for chopping livestock (Chopper) provides benefits to make it easier for farmers to produce good animal feed so that they can improve and accelerate livestock growth. The presence of Chopper in the "Loh-Jinawi" farmer group also has an impact: it saves the energy of farmers to find fodder, saves time in finding feed, feed waste becomes very small because the feed can be eaten by livestock cleanly, and livestock health is guaranteed because of the feed dishes to be better.